Spinal cord untethering after fetal myelomeningocele repair - Leopoldo Mandic Furtado; José Aloysio da Costa Val Vilho; José Antônio Lima Vieira; Aieska Kellen Dantas dos Santos (Brazilian Society for Pediatric Neurosurgery, 2021)
The incidence of tethered cord syndrome after myelomenigocele (MMC) repair is higher in patients undergoing in utero than postnatally. However, a paucity of studies have described the details of untethering in children which MMC was corrected during fetal life. In this technical note, we describe the spinal cord untethering of a girl after MMC in utero repair, highlighting the main steps regarding the anatomic recognition as well as neurophysiological monitoring finding role.